Effect of fiber reinforcement on color stability and degree of polymerization of different composite resins - Ozcan Karatas (Wolters Kluwer Medknow Publications, 2021)
Aim: The aim of this in vitro study was to determine the effect of fiber-reinforcement on the color changes and degree of polymerization of two different composite resins. Materials and Methods: A bulk-fill composite resin and a methacrylate-based composite resin with A2 shade were used in this study. Three groups of specimens (control group with no reinforcements, polyethylene fiber-reinforced composite and glass fiber-reinforced composite groups) were prepared from each composite. The color change of the specimens with polymerization was measured. Then, to determine the degree of polymerization, the hardness ratios were calculated by measuring the bottom and top surface hardness of all specimens. The data were analyzed by analysis of variance, Duncan's multiple range tests, and Independent sample t-test. Results: Statistical analysis of variance presented the significance difference between composite and fiber for color change (P < 0.05). The highest color change by polymerization was seen in the polyethylene fiber-reinforced bulk-fill composite group. It was found that the addition of fiber to composite resins significantly reduced the degree of polymerization (P < 0.05). Conclusion: The addition of fiber may lead to color change and reduce the degree of polymerization of composite resins. The amount of change may differ depending on the structural properties of the composite resins and fiber.